Performance Analysis of GaN/AlGaN HEMTs Passivation using Inductively Coupled Plasma Chemical Vapour Deposition and Plasma Enhanced Chemical Vapour Deposition Techniques - Kumar, Sunil; Malik, Amit; Rawal, Dipendra Singh; Vinayak, Seema; Malik, Hitendra (Defence Science Journal, 2018)
In the present paper SiN thin film has been studied as a passivation layer and its effect on AlGaN/GaN HEMTs is investigated using two different deposition techniques i.e PECVD and ICPCVD. AlGaN/GaN HEMTs devices passivated with optimised SiN film have delivered lower gate leakage current (from μA to nA). Device source drain saturation current (Ids) increased from 400mA/mm to ~550 A/mm and the peak extrinsic trans-conductance increased from 100 mS/mm to 170 mS/mm for a 0.8 μm HEMT device. The optimised SiN passivation process has resulted in reduced current collapse and increased breakdown voltage for HEMT devices.